Elasticity of Tourism Demand in the Modern World - BIRYUKOV, Vladimir Aleksandrovich; LIVSON, Maya Vladimirovna; FROLOVA, Victoria Borisovna; SKACHKO, Galina Aleksandrovna; DUKHOVNAYA, Liliya Leonidovna (Journal of Environmental Management and Tourism, 2019)
The article is devoted to the analysis of regularities of tourism demand formation in the modern world. It has been established that the high degree of demand differentiation provides tourists with the opportunity to choose products that are diverse in terms of quality, range of additional services and travel destinations. The authors have proved that tourists strive to independently select individual components, form tours and determine tour programs. It has been revealed that the remoteness of tourism demand in time and place from tourism supply necessitates premature planning of most tourist trips since the demand for most tourism products is seasonal. The authors have proposed to regulate the seasonality of demand for tourism services by various marketing measures, such as price differentiation and discounts, development of off-season types of recreation aimed at transferring part of the demand from the intensive season to another period, as well as reduction of the cost of tourism services.